FEATURES OF CHRONOTOPE IN “THE WORDS” BY JEAN-PAUL SARTRE - Mayilyan, Alvard (Armenian Folia Anglistika, 2024)
The article analyzes the features of the chronotope in the autobiographical novel “The Words” by the famous French writer Jean-Paul Sartre. The center of the analysis is the ways in which Sartre creates a complex and multi-layered domain of actions for his heroes, where time and space become not only physical but also philosophical realities. Particular attention is paid to how Sartre uses the chronotope to develop ideas of freedom, responsibility and existence. Through the analysis of everyday situations and the inner monologue of the main characters, the article reveals how the chronotope becomes an integral part of the concept of human existence in Sartre’s world.The article also analyzes the transformation of the classic chronotope in an autobiography, new manifestations of the spatiotemporal concept, as well as the chronotope of retrospective depiction through the author’s personal memories.
Keywords: existentialism; chronotope; spatiotemporal; memory; transfer; concept; freedom